2013
DOI: 10.1016/j.joca.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical nanocarrier association with chondrocytes and cartilage explants: influence of surface modification and extracellular matrix depletion

Abstract: Objective To evaluate cartilage diffusion and isolated chondrocyte association of micelles and liposomes and to determine the effect of cell-penetrating peptide (CPP) surface functionalization and extracellular matrix depletion on chondrocyte association and cartilage diffusion, respectively. Methods Rhodamine-labeled micelles and liposomes were incubated with bovine chondrocytes and cell-associated fluorescence was quantified using flow cytometry. Rhodamine-labeled CPP-modified micelles and liposomes were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…It is, therefore, critical to develop cartilage penetrating materials that, following IA administration, can enable rapid uptake of drugs through the full thickness of cartilage to reach a therapeutic level before being cleared out and bind within to increase joint residence time. Drug delivery systems under investigation include micron sized polymeric particles [17, 18], micelles [19, 20], liposomes [21, 22] and aggregating hydrogels [2325] but none of them have been shown to penetrate the cartilage and thus remain ineffective in eliciting a disease modifying biological response. Gene transfer vectors can only penetrate through the intact superficial zone of tissues [26] and suffer from concerns of immunogenicity and safety that make their clinical translation difficult [6, 27].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, critical to develop cartilage penetrating materials that, following IA administration, can enable rapid uptake of drugs through the full thickness of cartilage to reach a therapeutic level before being cleared out and bind within to increase joint residence time. Drug delivery systems under investigation include micron sized polymeric particles [17, 18], micelles [19, 20], liposomes [21, 22] and aggregating hydrogels [2325] but none of them have been shown to penetrate the cartilage and thus remain ineffective in eliciting a disease modifying biological response. Gene transfer vectors can only penetrate through the intact superficial zone of tissues [26] and suffer from concerns of immunogenicity and safety that make their clinical translation difficult [6, 27].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of particles have been explored in vitro and in vivo [1923] but the effects of particle size and surface morphology on their penetration, binding and retention within cartilage are less well understood [24]. The relative utility of 15 nm micelles vs. 138 nm liposomes was recently reported, showing the need to further differentiate between size and structure [25]. …”
Section: Introductionmentioning
confidence: 99%
“…The size of the drug carrier directly impacts its cartilage penetration ability41, 42; it has been shown that the exclusion size for avidin in cartilage is about 10 nm, 7 analogously Elsaid et al (2013) 40 gave evidence that 10 nm liposome were more effective than 100 nm micelle in delivery drugs into cartilage. The remarkable cartilage penetration ability exhibited by PBAE is despite their relative large size, that is in the order of hundreds of nanometers (Figure A6, Table 1); only few successful delivery systems for cartilage have sizes comparable to PBAE 12, 13.…”
Section: Discussionmentioning
confidence: 94%